The Distinctive Characteristics of Public Administration as the Hub of Every Human Organization: A Conceptual Analysis - Kumije , David (Kashere Journal of Politics and International Relations, 2023)
Since time immemorial, government and governmental agencies has continued to dominate the scope of human activities. While governmental functions includes the provision of leadership, maintaining order, providing public service, providing economic and national security as well as providing economic assistance, the actors that is the fulcrum and hub upon which these activities are implemented is Public Administration. Accordingly, Public Administration, which deals with the science of getting things done in the most efficient ways, will therefore continue to be a popular study and generate much interest. The objective of this paper is thus, to analyze the distinctiveness of this field; which is both an academic field of study and a profession. Public Administration is saddled with the task of planning, organizing, directing, coordinating and controlling the operations, workings and activities of a group of people. In x-raying this uniqueness, it was revealed that public administration is concerned with public policy and how it can be used to improve societal conditions. Thus, it focuses on providing services to the general public and ensures a good and safe life for people. At the end, it is revealed that Public Administration indeed permeates every facet of human existence because anywhere people live; there is a form of administration. That is why administrators are expected to cultivate the characteristics of tact and ingenuity.